Asma grave em crianças e adolescentes: fatores associados à exacerbação e evolução da função pulmonar - Monica Versiani Nunes Pinheiro de Queiroz (2016)
The objective of this study was to review the last 16 years of literature on the clinical and functional risk factors for asthma exacerbation, as well as on biochemical parameters in severe pediatric asthma refractory to treatment (SPART). In searches of the Cochrane/Brazilian Virtual Library of Health, Latin American and Caribbean Health Sciences Literature, Medline, Brazilian Office for the Advancement of Higher Education, and PubMed databases, we employed the following search terms/strings: severe asthma or refractory asthma or problematic asthma or difficult-to-treat asthma; exacerbation; risk factors or predictors; and pediatric or children and adolescents. We limited our searches to articles published between 1999 and 2016. We selected 26 original or review articles on severe pediatric asthma that addressed age, recent severe exacerbations, the level of asthma control, regular follow-up, comorbidities, behavioral factors, viral infection, passive smoking, biomarkers of inflammation, serum vitamin D levels, and pulmonary function. However, we found very few studies dealing with SPART. Severe asthma is a heterogeneous, dynamic disease in which the various predictors of exacerbation described assess different aspects of the disease and are complementary. Such factors should be analyzed from a multifactorial and individualized perspective, because many of them are potentially modifiable.